Initial Drug Regimen for Active Tuberculosis Cases in Montreal, 1995-1998 - Paul Rivest; Terry N Tannenbaum (Canadian Journal of Infectious Diseases)
OBJECTIVES: To evaluate the proportion of tuberculosis (TB) cases initially treated with the recommended four-drug regimen of isoniazid (INH), rifampin (RIF), pyrazinamide (PZA) and ethambutol (EMB) or streptomycin; and to identify factors associated with the choice of initial therapy.